187k views
5 votes
-4n-4+n+8=-6(-2n-4)+5(5-3n)

User Samrap
by
5.8k points

2 Answers

2 votes

Answer:

there is many possobiittys to this question. to answer i need to know what i am tring to find.

hope this helps

my yout_ube is vegangaming

User Shengy
by
5.7k points
3 votes

Answer:

There are no possible solutions BROTHER

Explanation:

Step 1: Simplify both sides of the equation.

−4n−4+n+8=−6(−2n−4)+5(5−3n)

−4n+−4+n+8=(−6)(−2n)+(−6)(−4)+(5)(5)+(5)(−3n)(Distribute)

−4n+−4+n+8=12n+24+25+−15n

(−4n+n)+(−4+8)=(12n+−15n)+(24+25)(Combine Like Terms)

−3n+4=−3n+49

−3n+4=−3n+49

Step 2: Add 3n to both sides.

−3n+4+3n=−3n+49+3n

4=49

Step 3: Subtract 4 from both sides.

4−4=49−4

0=45

User Prerna Chavan
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.